Concentration-temperature superposition principle for grain boundary migration in Ni(Cu) bicrystals. (June 2021) - Li, Jie; Yang, Xinhua; Wang, Peng; An, Qunli
Graphical abstract: Highlights: Concentration-temperature superposition is presented for the GB migration in alloys. GB migration main curve can be obtained at a reference temperature by shift factor. The superposition is validated by a comparison between predictions and MD results. Abstract: It is known that both the temperature and alloying element concentration have considerable effects on the GB migration in alloys. Analogous to the time-temperature superposition in viscoelasticity, the concentration-temperature superposition principle is presented for the GB migration in alloys. The GB migration displacement increased by elevating temperature can be achieved by reducing the alloying element concentration. A large number of molecular dynamics simulations are performed on Ni(Cu) bicrystal. The GB migration displacement is inversely proportional to the solute concentration and exponentially related to the temperature. The main curves at the reference temperature for different loading strains are constructed through a temperature-related shift factor. Finally, the validation is conducted by a comparison between its predictions and the simulation results.